(untitled) (Research, Society and Development, 2021)
In the present context, the demand for properties with a price below market value, has made the judicial auction an attractive option for the acquisition of goods. In this sense, this article aims to succinctly demonstrate which are the most common risks that the bidder will have when acquiring a residential property through a judicial auction. The subject has a broad legal panorama and multiple administrative rules, which for the bidder is of paramount importance to its analysis, planning and prior knowledge. The vast majority of auctioned properties are occupied, whether with the owner, tenants, third parties or invaders. This scenario immediately generates a concern for buyers, as the rights of the bidder are often unknown. This research presents an explanation of the functioning of auctions and an analysis of the factors that must be previously analyzed and verified before the auction. Through the findings evidenced in the research, it is possible to observe that the content presented does not exhaust the theme, as the diversity of interpretation and understanding of the judiciary is particular to each process, as evidenced by the interviewees. Through the present study, it can be concluded that despite the judicial auction having become an accessible form of real estate acquisition, however, the clearance of the property does not always proceed quickly and smoothly.